Dual length morphological model for bulk‐heterojunction, polymer‐based solar cells. Issue 5 (26th December 2013) - Shen, Hao; Zhang, Wenluan; Mackay, Michael E.
ABSTRACT We present a dual length morphological model for the active layer of bulk‐heterojunction, polymer‐based solar cells using results from neutron and X‐ray scattering techniques. Two critical characteristic lengths are found in the mixtures composed of poly(3‐hexylthiophene) (P3HT) and [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM). A characteristic length at 15 nm is the local characteristic of the P3HT crystals and PCBM agglomerations, which is independent of the bulk composition upon relaxation by thermal annealing. Conversely, a larger bicontinuous structure described by Teubner–Strey model with phase distances between 23 and 35 nm forms only after thermal annealing, which is highly correlated to the bulk compositions. These results suggest phase separation between the polymer and fullerene can only be partially manipulated by simple processing techniques such as coating conditions and annealing, and a more rigorous design of the morphology should be implemented in the future. © 2013 Wiley Periodicals, Inc. J Polym Sci Part B: Polym. Phys. 2014, 52, 387–396